Réponses

2014-03-17T13:06:53+01:00
Bonjour,

1) (uv)'=u'v+uv'\\\\\ [u(x)v(x)]\limits_a^b=\int\limits_a^b[u'(x)v(x)+u(x)v'(x)]dx\\\\\ [u(x)v(x)]\limits_a^b=\int\limits_a^bu'(x)v(x)dx+\int\limits_a^bu(x)v'(x)dx\\\\\ [u(x)v(x)]\limits_a^b-\int\limits_a^bu'(x)v(x)dx=\int\limits_a^bu(x)v'(x)dx\\\\\ \int\limits_a^bu(x)v'(x)dx=[u(x)v(x)]\limits_a^b-\int\limits_a^bu'(x)v(x)dx

2) a) I=\int\limits_0^1x.e^xdx\\\\u(x)=x\Longrightarrow u'(x)=1\\\\v'(x)=e^x\Longrightarrow v(x)=e^x\\\\I=[x.e^x]\limits_0^1-\int\limits_0^11.e^xdx\\\\I=[x.e^x]\limits_0^1-\int\limits_0^1e^xdx\\\\I=[x.e^x]\limits_0^1-[e^x]\limits_0^1\\\\I=[x.e^x-e^x]\limits_0^1\\\\I=[e^x(x-1)]\limits_0^1

I=e^1(1-1)-e^0(0-1)\\\\I=0-1\times(-1)\\\\I=1


J=\int\limits_1^ex^2ln(x)dx\\\\u(x)=ln(x)\Longrightarrow u'(x)=\dfrac{1}{x}\\\\v'(x)=x^2\Longrightarrow v(x)=\dfrac{x^3}{3}\\\\J=[\dfrac{x^3}{3}.ln(x)]\limits_1^e-\int\limits_1^e\dfrac{1}{x}.\dfrac{x^3}{3}dx\\\\J=\dfrac{1}{3}[x^3.ln(x)]\limits_1^e-\dfrac{1}{3}\int\limits_1^ex^2dx\\\\J=\dfrac{1}{3}[x^3.ln(x)]\limits_1^e-\dfrac{1}{3}[\dfrac{x^3}{3}]\limits_1^e\\\\

J=\dfrac{1}{3}[x^3.ln(x)-\dfrac{x^3}{3}]\limits_1^e\\\\J=\dfrac{1}{3}[\dfrac{3x^3.ln(x)-x^3}{3}]\limits_1^e\\\\J=\dfrac{1}{9}[3x^3.ln(x)-x^3]\limits_1^e\\\\J=\dfrac{1}{9}[x^3(3ln(x)-1)]\limits_1^e\\\\J=\dfrac{1}{9}[e^3(3ln(e)-1)-1^3(3ln(1)-1)]\\\\J=\dfrac{1}{9}[e^3(3\times1-1)-1\times(3\times0-1)]\\\\

J=\dfrac{1}{9}[2e^3+1]

b) \int ln(x)dx=\int 1\times ln(x)dx\\\\u(x)=ln(x)\Longrightarrow u'(x)=\dfrac{1}{x}\\\\v'(x)=1\Longrightarrow v(x)=x\\\\\int ln(x)dx=xln(x)-\int\dfrac{1}{x}.xdx\\\\\int ln(x)dx=xln(x)-\int1dx\\\\\int ln(x)dx=xln(x)-x+C\ \ (C=constante)

Les primitives de ln(x) sont de la forme F(x) = x.ln(x) - x + C (C = constante)

Or F(1) = 0 ==> 1.ln(1) - 1 + C = 0
                 ==> 1 * 0 - 1 + C = 0
                 ==> -1 + C = 0
                 ==> C = 1

Par conséquent, la primitive de ln(x) qui s'annule en 1 est définie par F_1(x)=x.ln(x)-x+1